The Banded-wing Moselia infuscata (Claassen) Phenotype from California and Oregon, U.S.A. (Plecoptera: Leuctridae) - Gill, Brian A.; Kondratieff, Boris C.; Stark, Bill P.; Sandberg, John B. (Zootaxa, 2015)
Moselia specimens from California and Oregon with a banded-wing phenotype were found to be indistinguishable morphologically from those of M. infuscata (Claassen) with typical wing pigment pattern. Preliminary DNA barcode data (Cytochrome c Oxidase subunit I [COI]), however, show significant genetic variation among four populations including three from northern California sites and one from southern Oregon. Although this genetic variation exceeded standard divergence thresholds often used to recognize distinct stream insect species, no new taxa are proposed at this time due to the preliminary nature of the data.